Excavated features (Scottish Historical and Archaeological Internet Reports, 2025)
Archaeological excavations conducted in 2017 at Grantown Road, Forres form the final phase of works on a residential development that began in 2002. The earlier works examined an area of more than 70ha and confirmed the presence of an extensive Iron Age settlement represented by ring-ditch, ring-groove, and post-ring structures, in association with four-post structures, a souterrain, and metalworking furnaces. The 2017 works (Canmore ID 320363), reported here, have expanded the record of prehistoric and medieval settlement in the area and revealed that a previously recorded cropmark site represented an Iron Age enclosure with a single post-ring roundhouse. Also identified in the present works were an Early Neolithic post-ring structure and a series of pits dating from the Neolithic to the medieval periods with artefact assemblages of pottery, lithics, and stone tools, including a rare fragment of a locally made mortar dated to the 13th century ad.